Mineralocorticoid Receptor Antagonists in Primary Aldosteronism - Stavropoulos, Konstantinos; Papadopoulos, Christodoulos; Koutsampasopoulos, Konstantinos; Lales, Georgios; Mitas, Christos; Doumas, Michael (Current Pharmaceutical Design, 2018)
Background: Primary aldosteronism is the most common causes of secondary hypertension. Patients suffering from this clinical syndrome have an increased cardiovascular risk and target organ damage. Mineralocorticoid receptor antagonists are the optimal pharmaceutical option for the management of such patients. Objectives: The study aimed to assess the effects of mineralocorticoid receptor antagonist in the treatment of patients with primary aldosteronism. Method: We conducted an in-depth review of the literature and comprehensive identification of the clinical studies investigating the efficacy of mineralocorticoid receptor antagonists in individuals with primary aldosteronism. Results: Mineralocorticoid receptor antagonists result in significant improvement in blood pressure and serum potassium level among patients with primary aldosteronism. Moreover, mineralocorticoid receptor antagonists reverse left ventricular hypertrophy, albuminuria, and carotid intima-media thickness. However, a high risk for atrial fibrillation remains among subject with primary aldosteronism in such agents. Conclusion: Mineralocorticoid receptor antagonists are recommended as the first-line treatment in patients with bilateral primary aldosteronism. In patients with unilateral aldosterone-producing adenoma, adrenalectomy should be preferred. However, existing data presents significant limitations and is rather inconclusive. Future randomized control trials are required in order to illustrate the field.
Keywords: cardiovascular risk